Promotores de crecimiento (promotor l y promotor 43) en Aves de Postura de la línea hy - line brown desde el 1 día hasta las 16 semanas de vida, en la Parroquia de San Buenaventura, Cantón Latacunga, Provincia de Cotopaxi. - Panchi Sinchiguano, Verónica Paulina (2014)
This research Evaluation of two growth promoters (Promoter and Promoter L 43) in laying pullets Hy-Line Brown Line 1 day to 16 weeks of age in the Parish of San Buenaventura, Canton Latacunga, Cotopaxi Province, is performed to give an alternative to laying food to improve animal production in the case of birds. Experimentally applied research in the shed being used 180 laying pullets one day old with an average weight of 30 g. Upon arrival pesos daily treatments for the administration of the two promoters in the drinking water for a period of 16 weeks were recorded. The chicks were randomly distributed into nine compartments in a number of 20 birds per treatment. Treating one with 1 ml/l of L promoter according to body weight per bird was applied daily. Two-treatment with 1 g/l of 43 according to promoter Live bird weight per day, and in the treatment three, which is the control group only growth promoters Biomentos balanced brand was applied. In the experiment design was completely randomized blocks (DCA) with three treatments and three replications was applied. In interpreting the results of analysis of variance and Duncan's test were performed. According to the results we can determine the best data regarding weight gain is the Treatment 3 (control), reaching an average of 1387.06 superior gr. We analyzed the non-administration of the promoters was excellent in weight gain. While, Treatment 1 (1ml/l of L+Water Promoter) reached an average of 1370.68 gr. And Treatment 2 (1g/l of developer 43+water) with 1205.10 g. It was found that no further increase in weight obtained in the layer chicks with respect to the control treatments and 1. As feed conversion in the control treatment averaged 2.79 gr. While in treatment 1 average was obtained 2.70 g., In the treatment 2 were 2.38 gr. Through economic analysis through the Benefit/Cost indicator, taking into consideration the weight up, it was determined that the increased profitability was achieved in the control treatment, with a profit of $ 0.97 per bird. While in the treatment (T1) and (T2) was a profit of $ 0.87 per bird. Therefore, by not using any promoter outperformance is achieved.